ECHINODERM FAUNA OF THE LEMBEH STRAIT, NORTH SULAWESI: INVENTORY AND DISTIBUTION REVIEW - Supono, -; Lane, David J. W.; Susetiono, - (Marine Research in Indonesia, 2014)
Indonesia is particularly rich in Echinoderms and North Sulawesi lies at the geographic centre of this biodiverseÃÂ marine realm. While further studies on Sulawesi Echinodermata are required in order to obtain full understanding ofcurrent biodiversity status, preliminary SCUBA and intertidal surveys in early 2012 in the vicinity of the LembehÃÂ Island, a region little explored previously, recorded a total of 76 species of 4 classes (Asteroidea, Ophiuroidea,ÃÂ Echinoidea and Holothuroidea) from shallow waters (0-40 m) at 36 sites (sea grass, coral rubble and reef). TheÃÂ class Crinoidea is not reported here. A review of Echinoderm literature for North Sulawesi noted that there are 114ÃÂ species belonging to 5 classes of Echinodermata.